2021
DOI: 10.1177/13524585211032801
|View full text |Cite
|
Sign up to set email alerts
|

Impaired motion perception is associated with functional and structural visual pathway damage in multiple sclerosis and neuromyelitis optica spectrum disorders

Abstract: Background: Decreased motion perception has been suggested as a marker for visual pathway demyelination in optic neuritis (ON) and/or multiple sclerosis (MS). Objectives: To examine the influence of neuro-axonal damage on motion perception in MS and neuromyelitis optica spectrum disorders (NMOSD). Methods: We analysed motion perception with numbers-from-motion (NFM), visual acuity, (multifocal (mf)) VEP, optical coherence tomography in patients with MS ( n = 38, confirmatory cohort n = 43), NMOSD ( n = 13) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The deficiency of NFL is related with the progression of ON. Several studies have indicated that NFL and NFM are significantly downregulated in the eyes of the patients with ON, and the expression of NFL has always been selected as a biomarker for the diagnosis of optical system [ 22 , 23 ]. These proofs suggest that GAP-43 could induce the differentiation of BMSCs into RGC-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…The deficiency of NFL is related with the progression of ON. Several studies have indicated that NFL and NFM are significantly downregulated in the eyes of the patients with ON, and the expression of NFL has always been selected as a biomarker for the diagnosis of optical system [ 22 , 23 ]. These proofs suggest that GAP-43 could induce the differentiation of BMSCs into RGC-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring motion perception, another type of visual assessment, may predict both axonal loss and demyelination, though without regional specificity. A study by Ayadi et al (2021) investigated two cohorts of people with MS in Berlin and Sydney and found that motion perception deficits correlated with RNFL and GCIPL thicknesses and visual acuity. This suggests that motion perception may be correlated with axonal loss.…”
Section: Monitoring Ms Through the Visual Systemmentioning
confidence: 99%
“…This suggests that motion perception may be correlated with axonal loss. However, in the cohort from Sydney, where patients had more pronounced optic neuritis, motion perception also correlated with mfVEP latencies ( Ayadi et al, 2021 ). This is consistent with a study showing that, especially in patients with a history of optic neuritis, full-field VEP latencies were inversely associated with motion perception ability ( Backner et al, 2019 ).…”
Section: Monitoring Ms Through the Visual Systemmentioning
confidence: 99%
See 2 more Smart Citations